Peningkatan Motivasi Berwirausaha dan Mutu Usaha Mikro Melalui Pelatihan Berbasis Konsep Magnet Rejeki - Arif Julianto Sri Nugroho; Anis Marjukah; M Pujo Darmo; Dandang Setyawanti; Agung Nugroho Jati; Cahaya Nugrahani; Jarot Prasetyo (Journal of Dedicators Community, 2021)
Self-business micro which can live, survive through generation, and reach the dream is the expectation from the owner. There are many factors which can determine the success of the businessman to fight from the competition. One factor is the ability to respond the internal and external changes rapidly and exactly. The ability to win the competition, the ability to read the situation, the ability to collaborate with other to have a synergy, and the ability to adapt from the competition are the keys toward the business sustainability. This community service aims to test the model of business training based on the concept of magnet rejeki which can give a significant influence toward the motivation of micro business. The method of the study is development model by entrepreneurship training that are integrated input by including the businessman on factors which influence their motivation in the beginning of their business, the business motivation training based on the concept of magnet rejeki, and visit business collaboration and monitoring. The result of this study give the conclusion that the business training based on the concept of magnet rejeki is effective to conduct by the proof that there is an increase of motivation to have a business and business profit after the training.